2016
DOI: 10.1103/physrevphyseducres.12.020132
|View full text |Cite
|
Sign up to set email alerts
|

Open-ended versus guided laboratory activities:Impact on students’ beliefs about experimental physics

Abstract: Improving students' understanding of the nature of experimental physics is often an explicit or implicit goal of undergraduate laboratory physics courses. However, lab activities in traditional lab courses are typically characterized by highly structured, guided labs that often do not require or encourage students to engage authentically in the process of experimental physics. Alternatively, open-ended laboratory activities can provide a more authentic learning environment by, for example, allowing students to… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
58
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 80 publications
(62 citation statements)
references
References 22 publications
1
58
1
Order By: Relevance
“…Another possible claim is that the lab increases student motivation, which then is reflected in improved overall course performance. Studies of both concepts-based and structured lab courses, however, have shown that student attitudes and motivation towards experimental physics decrease by the end of such courses [15,27]. Regardless of whether the learning in the lab leads to improved learning in other aspects of the course, what we have shown is that these labs are not…”
Section: Discussionmentioning
confidence: 53%
See 4 more Smart Citations
“…Another possible claim is that the lab increases student motivation, which then is reflected in improved overall course performance. Studies of both concepts-based and structured lab courses, however, have shown that student attitudes and motivation towards experimental physics decrease by the end of such courses [15,27]. Regardless of whether the learning in the lab leads to improved learning in other aspects of the course, what we have shown is that these labs are not…”
Section: Discussionmentioning
confidence: 53%
“…Research has shown that even small elements of open endedness in activities can improve student attitudes towards experimental physics [15]. Providing students with time, opportunity, and incentive to revise, troubleshoot, or explore by, for example, spreading a single lab experiment across multiple weeks may enable the desired skills focus [34,45].…”
Section: Midterm Exammentioning
confidence: 99%
See 3 more Smart Citations